Individual voices, shared experience: the power of knowledge, caring, and understanding in student teacher relationships - Eickhoff, Shannon (Kansas State University, 2022)
Ethics of care, applied to women’s psychology, education, and Black Feminist Thought, provides the framework for this research endeavor. This feminist approach calls us to critically consider our historical model of education based on competitive, masculine ideals which fail to attend to the individual needs of students. Using the philosophical lenses of Nel Noddings’ ethics of care in education, bell hooks’ engaged pedagogy, Carol Gilligan’s feminist ethics of care, and Patricia Hill Collins’ Black Feminist Thought, this work created a framework to better understand the powerful effects of caring student teacher relationships. Using narrative inquiry as methodology, this research was guided by storytelling in the form of journals gathered over a twenty-five-year period. The stories themselves serve as the framework for understanding individual voices as well as a collective consciousness illustrating how our students are faring in American schools today. The results of this research provide living examples of the individual philosophical tenets articulated by Noddings, hooks, Gilligan, and Hill Collins. The significance is found in its potential benefit to teachers, administrators, and all those who work with students by offering a new lens through which to view our current philosophical and pedagogical practices as well as the opportunity to recognize the powerful ability of students’ stories to take us to a much deeper place of understanding.
Keywords: Ethics of care; Feminism; Engaged pedagogy; Black feminist thought; Student teacher relationships; Storytelling